From start-up to buy-out : the changing descriptions of innovation and employee jobs through the fintech life-cycle - Kleinsmith, Niela, (SAGE Business Cases., 2018)
In September 2017, Nicolas Weber, a web designer and manager for Bank in My Pocket (BMP), a former fintech start-up acquired by a large commercial bank, assessed the evolution of the company he had helped to build. Over the course of the start-up's development and repetitive acquisitions and mergers, within successively larger traditional banks, a few of the original job qualities that had attracted him to BMP remained. But many more had changed. The very definition of 'innovation' had mutated to something that was increasingly hard to reconcile with his notion of a fintech start-up. Pushed by a skilled colleague's recent departure, with HR making no effort to retain her, Weber evaluated his company's current stance on a number of HR and innovation issues. Like his colleague, changing employers was a tempting idea.